Kamuflase: Korelasi Intramusikal dan Ekstramusikal dalam Penciptaan Komposisi Karawitan Bali - Yan Priya Kumara Janardhana (Institut Seni Indonesia Denpasar, 2021)
Purpose: This paper aims to examine more deeply the implementation of the meaning of camouflage events on the textual execution of compositions. Janu Janardhana as the composer of â€œCamouflageâ€, interpreted the camouflage event as changing colors, attitudes and shapes according to the time and place. Research methods: The author chooses a qualitative method because the phenomena experienced by the subject (composer) can be described holistically, because the writer is a composer of Camouflage's work itself. With qualitative methods, the authors know about how rhythm, tone, melody, tempo, dynamics, timbre and composition structure work according to camouflage events that occur in animals. Results and discussion: Camouflage is a musical composition for gamelan that uses Balinese gamelan characteristics as the main material for cultivating the intramusical aspect. The characteristics referred to are the waves and the variety of tuning systems found in Balinese gamelan. The various types of waves, namely, a slow contributor, a pengumbang, a bugger, a pengejer, and a siep can be achieved in one piece of work by utilizing the variety of saih / tuning systems found in Balinese gamelan. The varieties of saih are, saih ageng (gong gede saih pitu), saih madya (gamelan semaradhana), and saih alit (gamelan semara pegulingan). Implication: In extramusical terms, the composition of Camouflage music is inspired by a biological phenomenon in animals called camouflage. For example, the color changes made by chameleons and octopuses when moving, and changes in the color, attitude, shape and structure of the skin of cianea octopus when threatened by predators.